2017
DOI: 10.5709/acp-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Practice-Related Reductions of Dual-Task Interference with Simple Tasks: Data and Theory

Abstract: In dual-task situations, interference between two simultaneous tasks impairs performance. With practice, however, this impairment can be reduced. To identify mechanisms leading to a practice-related improvement in sensorimotor dual tasks, the present review applied the following general hypothesis: Sources that impair dual-task performance at the beginning of practice are associated with mechanisms for the reduction of dual-task impairment at the end of practice. The following types of processes provide source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 107 publications
4
38
0
Order By: Relevance
“…The cost was comparable across SOAs. Lien et al (2003) concluded from the switch costs in T2 that time is needed for processes involved in the disengagement of T1 and the engagement of T2, and thus, that the shifting component is involved in dual-tasking (see also Liepelt, Strobach, Frensch, & Schubert, 2011, for similar conclusions derived from studies on practice effects in dual-tasking; for a review, see, e.g., Strobach & Schubert, 2017). They argued that the missing absorption of switch costs in T2 during the waiting period for the availability of the response-selection bottleneck (i.e., additivity of SOA and T1-T2 transition) suggests that these processes, at least partially, occur after response selection for T1 and before response selection for T2, and modified the response-selection bottleneck accordingly.…”
Section: Relating Task-switching and Dual-taskingmentioning
confidence: 92%
“…The cost was comparable across SOAs. Lien et al (2003) concluded from the switch costs in T2 that time is needed for processes involved in the disengagement of T1 and the engagement of T2, and thus, that the shifting component is involved in dual-tasking (see also Liepelt, Strobach, Frensch, & Schubert, 2011, for similar conclusions derived from studies on practice effects in dual-tasking; for a review, see, e.g., Strobach & Schubert, 2017). They argued that the missing absorption of switch costs in T2 during the waiting period for the availability of the response-selection bottleneck (i.e., additivity of SOA and T1-T2 transition) suggests that these processes, at least partially, occur after response selection for T1 and before response selection for T2, and modified the response-selection bottleneck accordingly.…”
Section: Relating Task-switching and Dual-taskingmentioning
confidence: 92%
“…From a perspective of executive processes, dual-task performance data may thus point to a set of well-identifiable task coordination processes. Recent studies investigated, for example, the impact of practice (e.g., Strochbach and Schubert, 2017 ), age (e.g., Maquestiaux, 2016 ), compatibility of stimulus and response information (e.g., Hazeltine et al, 2006 ), or recently experienced conflict (e.g., Janczyk, 2016 ) on dual-task performance and executive functioning in dual-tasks. In the following section, we provide a brief overview on papers of the present research topic aiming to contribute to the further specification of executive functions implicated in dual-tasking.…”
Section: Dual-task Paradigms Theories and Executive Functioningmentioning
confidence: 99%
“…While visual perception demonstrates successful divided attention under desirable conditions (Shiffrin & Schneider, 1977), dual-task performance is often subject to stubborn limitations. These limitations arise even when the component tasks are simple (Vince, 1948) and sometimes even after participants receive extensive practice (Ruthruff, Johnston, & Van Selst, 2001;Strobach & Schubert, 2017). The overall goal of the present study is to better understand the nature of dual-task interference.…”
Section: Introductionmentioning
confidence: 99%